(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of low back pain and its associated risk factors among the population aged 35-60 in Hue city. Methods: A cross-sectional descriptive study was conducted on 682 residents across four wards of Hue city. Data were collected from September 2022 to September 2023. Results: The prevalence of low back pain among the study participants was 42.5%, with a higher proportion in females (60%) than in males (40%). Regarding occupational characteristics, the majority of participants engaged in work involving prolonged standing, sitting, or bending (43.7%) and heavy lifting or carrying (39.3%). Pain onset occurred primarily during work (33.8%), daily activities (28.2%), and weather changes (20%). Functional disability assessment using the ODI indicated that minimal disability accounted for the majority (71%); however, nearly 9.7% of subjects suffered from severe disability, crippling pain, or were bed-bound. Regarding health-seeking behavior, 43.1% of patients visited medical facilities for examination. Treatment methods included prescription medication (66.4%), traditional medicine therapies (33.6%), self-medication with analgesics (20%), and no treatment (6.4%). Regarding treatment outcomes, 85.6% reported pain relief but experienced frequent recurrences, 9.6% showed no improvement, and only 4.8% fully recovered. Conclusion: The prevalence of low back pain among residents aged 35-60 in Hue city was relatively high (42.5%). The study found statistically significant associations (p < 0.05) between low back pain and age group, socio-economic status, occupational characteristics and history of musculoskeletal disorders.